Isolation of Dihydroflavonol-4-reductase (DFR) Gene in Dendrobium helix cv. Pomeo Brown - Anggraini, Riska; Febriani, Ayu Linda; Mazieda, Mutia Naila; Al-Yamini, Thobib Hasan; ., Dahlia; Listyorini, Dwi (KnE Life Sciences, 2017)
Dendrobium helix cv. Pomeo Brown is one of the most attractive species in Spatulata section. This orchid is an epiphyte which has clustered stem, elliptic leaves, and erected flowers with brown petals. The brown color of D. helix cv. Pomeo Brown is due to the anthocyanin. Biosynthetic pathway of anthocyanin is regulated by several enzymes, including key enzyme dihydroflavonol-4-reductase (DFR) which is encoded by DFR gene. This study aimed to analyze the DFR gene from D. helix cv. Pomeo Brown by PCR using primer which were designed based on Dendrobium moniliforme. The sequences amplified using these primers could not be analyzed. Based on the sequence chromatograph, it can be suggested that the amplified DNA consists of several DFR fragments. Keywords: Dendrobium helix cv. Pomeo Brown; anthocyanin; DFR gene.